2021
DOI: 10.34172/aim.2021.47
|View full text |Cite
|
Sign up to set email alerts
|

Prognostic Factors Associated with Survival in Patients Infected with COVID-19: A Retrospective Study on 214 Patients from Iran

Abstract: Background: Decision-making on allocating scarce medical resources is crucial in the context of a strong health system reaction to the coronavirus disease 2019 (COVID-19) pandemic. Therefore, understanding the risk factors related to a high mortality rate can enable the physicians for a better decision-making process. Methods: Information was collected regarding clinical, demographic, and epidemiological features of the definite COVID-19 cases. Through Cox regression and statistical analysis, the risk factors … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 14 publications
0
4
0
Order By: Relevance
“…At the initial examination, 6462 studies were obtained, which were screened and evaluated layer by layer according to inclusion and exclusion criteria, and 49 studies were finally included, most of which were retrospective studies, from 10 countries, with a total of 23,611 COVID-19 patients, including 9357 cases complicated with liver injury. [7–55] The flow chart of literature screening is shown in Figure 1. The basic characteristics of the included literature are shown in Table 1.…”
Section: Resultsmentioning
confidence: 99%
“…At the initial examination, 6462 studies were obtained, which were screened and evaluated layer by layer according to inclusion and exclusion criteria, and 49 studies were finally included, most of which were retrospective studies, from 10 countries, with a total of 23,611 COVID-19 patients, including 9357 cases complicated with liver injury. [7–55] The flow chart of literature screening is shown in Figure 1. The basic characteristics of the included literature are shown in Table 1.…”
Section: Resultsmentioning
confidence: 99%
“…Pre-existing comorbidities have also been associated with an increased risk of ICU admission. Sadeghi and colleagues reported that patients with a history of kidney diseases or cancer were at a higher risk of being admitted to the ICU (P = 0.04, OR = 2.54, 95% Cl = 1.00-6.41 and P = 0.00, OR = 3.15, 95%Cl = 1.39-7.15; respectively) [31]. Other comorbidities such as hypotension, Type 2 Diabetes Mellitus, Chronic Kidney diseases, and Heart failure have also been associated with an increased risk of ICU admissions [30].…”
Section: Discussionmentioning
confidence: 99%
“…The difference in these studies can be attributed to the fact that they mostly included patients with severe in uenza and COVID-19.It is important to note that several factors may have impacted the ICU admissions in both COVID-19 and In uenza patients. Univariate analysis of risk factors associated with ICU admission by Sadeghi and colleagues showed that age was signi cantly associated with the increased risk of ICU admission among COVID-19 patients (OR: 1.02; 95% CI: 0.89 to 0.89; p = 0.03)[31]. This nding is evident in a German cohort study that reported the highest percentage of COVID-19 ICU admissions among patients in the 70-89 age group (64%) and the least percentage in the 20-49 age group (< 1%)…”
mentioning
confidence: 99%
“…The etiology of problems are airway hypersecretion and inflammatory processes (associated condition: respiratory tract infection). The nursing problem is integrated with the findings, such as 1) the majority of respondents with cough by 45.45-80.00%; 2) the majority of respondents with dyspnea by 50.90-80.00%; 3) increased work of breathing and shortness of breath; 4) productive cough by 35.07% of respondents; 5) the mean of respiratory rate (RR) was 29.30 bpm with standard deviation of 7.21 bpm; 6) respiratory rate >24 bpm by 70% of respondents; 7) pulmonary auscultation was rhonchi in bilateral lungs; 8) the median of C-reactive protein was 55.30 mg/L (minmax: 11.32-124.53); 9) the median of Procalcitonin was 0.21 ng/mL (0.16-0.26); 10) the median of Interleukin 6 was 46.18 pg/ml (min-max: 27.39-150.40); 11) chest CT scan showed ground-glass opacity (GGO) of 100% respondents Chest X-ray showed bilateral lung opacities on perihilar and middle to inferior lung fields; 12) bronchoscopy result (at fourteen hospitalizations) showed a very thick mucous plug on the right and left main bronchus (Gul et al, 2021;McGovern et al, 2020;Sadeghi et al, 2020;Widysanto et al, 2020;Zeng et al, 2020;L. Zhang et al, 2020).…”
Section: Ineffective Airway Clearancementioning
confidence: 99%